A Rare Case of Postpartum Carotid Dissection - Marzie Abutorabi Zarchi; Amirmasoud Kazemzadeh Houjaghan (Case Reports in Clinical Practice)
Cervicocranial arterial dissection is not a common disease (2.5% of total brain infarction), and its pathogenesis is still not fully understood. However, it appears to be multifactorial and is rarely seen in the postpartum period. A 40-year-old woman presented to the emergency department with sudden right lower limb paresis 10 days after vaginal delivery. She had no history of DM, HTN, preeclampsia, or underlying cerebrovascular disease. Upon evaluation, left extracranial carotid artery dissection was found on cervical MRA. The likelihood of postpartum dissection is rare, but it could be due to vascular damage associated with the Valsalva maneuver during labor; hemodynamic and hormonal changes due to pregnancy may also play a role.